T-wave depletion and bradycardia possibly secondary to acute pancreatitis: Review of the literature - Cansel TÜRKAY,; Timuçin AYDOĞAN,; Aydın KARANFİL,; Mehtap ERKMEN UYAR,; Yusuf SELÇOKİ,; Mehmet KANBAY, (Turkish Journal of Gastroenterology, 2019)
-